Cerebral Embolic Protection in Patients Undergoing Left Atrial Appendage Closure - Julia Seeger; Philipp Seppelt; Mario Iturbe-Orbe; David Leistner; Jochen Wöhrle; Michael Joner (Journal of Cardiovascular Development and Disease)
(1) Background: Cerebral magnetic resonance imaging has reported new cerebral ischemic lesions after left atrial appendage (LAA) closure in about one- third of patients. Stroke occurs predominantly periprocedurally. This study evaluated the characteristics of embolized debris captured by the SENTINELTM cerebral embolic protection system in patients undergoing LAA closure; (2) Methods: Sixty filters of 30 consecutive patients undergoing LAA closure with the WATCHMAN FLXTM device were collected and captured debris was analyzed by histopathology and histomorphometry. Clinical outcome measures were disabling and non-disabling stroke within 72 h; (3) Results: In most filters, no material was captured. The predominant captured debris was acute or organized thrombi. The most common pattern was acute fibrin-rich thrombus, which was detected in 11/30 (33.3%) patients. Particles of heart tissue were seen in 6/30 (20%) patients, and foreign material was seen in one (3.3%) patient. The number of particles ranged from 0 to 52 per patient with a maximum of 31 in the distal and 21 in the proximal filter. Particle diameter ranged from 131 to 2614 µm. By logistic regression analysis, only protected time remained a multivariable predictor for larger particles (p = 0.039). There was no disabling or non-disabling stroke. Compared to transfemoral aortic valve replacement, the number of particles is only about 1.5%. (4) Conclusion: LAA occlusion with the WATCHMAN FLXTM was associated with a very low number of embolized particles captured with the double-filter SENTINELTM embolic protection system and no periprocedural stroke.